A quantitative connection between shear band mediated plasticity and fracture initiation toughness of metallic glasses. (15th May 2018) - Narayan, R.L.; Raut, Devaraj; Ramamurty, U.
Abstract: While it is well recognized, albeit qualitatively, that shear band mediated plasticity ahead of crack or notch tips is the raison d'être for the high fracture toughness of 'ductile' bulk metallic glasses (BMGs), quantitative connection between those two material properties is yet to be established. In an attempt to study this, we examine if mode I fracture initiation toughness, K Ic, of a number of BMGs can be related to the shear band number, N i, which is a discretized measure of plasticity in MGs, around spherical indentation impressions that are made to a fracture mechanism based predetermined indentation strain. Results show that K Ic scales with ( N i ) 3/2 . Then, the relation between the shear band density in the notch tip plastic zone, N n, and K Ic is examined, which shows that a power law: K Ic ∝ ( N n ) 1/2, captures the data reported in literature for a number of BMGs. This result confirms that it is indeed the notch tip plasticity that determines K Ic of BMGs. The power law exponent of 0.5 is rationalized by recourse to elasto-plastic fracture mechanics. Possible connections between N i and N n, ways of enhancing the latter so as to increase K Ic, and the central role played by the relative density of MGs in determining both elastic, plastic, and fracture responses are discussed. Graphical abstract: Image 1